Staff Development to embed inclusive learning for profoundly deaf learners in further education - Rodgers, Rob (2007)
Inclusive learning for pupils and learners with Special Educational Needs (SEN) is being championed widely within the education sector, both in the compulsory and the post-compulsory stages. The context for this thesis is an exploration of how staff in the further education sector can be best prepared through staff development to support profoundly deaf learners. The thesis concentrates on the subject specialist who has the skills and experience to deliver their own subject but may not have the skills to deliver the subject to deaf learners.